The Influence of 1 V 1 Athlete Matches on Decision-Making in Futsal - Kevin Fernaldy Shelby; Komarudin; Mona Fiametta Febrianty (Universitas Negeri Semarang, 2025)
This study aims to examine the effect of situational training, specifically 1v1 training, on improving the decision-making abilities of futsal players. The study design used an experimental method with a pretest-posttest control group model and involved 12 players from the Bandung Icon FC futsal club. The instrument used was the GPAI (Game Performance Assessment Instrument), and measurements were conducted quantitatively based on data on successful decision-making during matches. Normality and homogeneity tests were used to analyze the data, as well as paired and independent t-tests. The findings revealed that 1v1 training greatly enhanced participants' decision-making, as indicated by an increase in success rates from 33% to 84% in the experimental group. In comparison, the control group saw no notable changes. These findings support the efficacy of real-world and simulation-based training in improving players' cognitive, technical, and psychological skills, as well as strengthening brain connections in the automated decision-making process. The study's key finding is that incorporating situational training into futsal training regimens on a regular basis is critical for improving performance and competitiveness.